ENZYME-ENHANCED EXTRACTION OF CAMPTOTHECIN AND ITS ANTICANCER ACTIVITY ON BREAST CANCER CELL LINE - Natarajan, Sujatha; Alagar Yadav, Sangilimuthu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Camptothecin (CPT) is an alkaloid produced by endophytic fungi, and it acts against colon, uterine, and lung cancers as drug. Macerating enzyme cellulase is used to increase the extraction yield of CPT. The cytotoxicity and anticancer activity of CPT are being studied to aid in discovering its beneficial properties and its use as a lead compound in pharmacological industries. Methods: In this work, the extraction of CPT from the endophytic fungi is enhanced using the crude enzyme cellulase obtained from Aspergillus niger. CPT was extracted from A. niger by two ways such as using macerating enzyme cellulase (CWME) and without macerating enzyme (CWOME). High-performance liquid chromatography (HPLC) was carried out to characterize the extracted CPT against standard CPT. The yields of CPT extracted both ways were compared. Cytotoxicity of the extracted CPTs was studied against Vero cells. The anticancer activity of CPT was tested against the breast cancer cell line (MCF7). Results: The extracted compound was confirmed to be CPT using HPLC. The yield of CPT extracted with enzyme was more than that extracted without enzyme. The extracted CPT was found to be safe up to 1000 Î¼g/ml against Vero cells. The IC50 value of the CWME was found to be 62.5 Î¼g/ml compared to the CWOME (IC50 125 Î¼g/ml) against the MCF7 cell line, thus inferring that the anticancer activity of CWME was higher than that of CWOME. Conclusion: Thus, it can be concluded that cellulase helps to increase the extraction yield of CPT from A. niger. CPT is safe against normal cell line and exhibits anticancer properties against MCF7.